2019
DOI: 10.3892/ijo.2019.4750
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in MnSOD promotes the migration and invasion of squamous carcinoma cells

Abstract: Reactive oxygen species (ROS) homeostasis is maintained at a higher level in cancer cells, which promotes tumorigenesis. Oxidative stress induced by anticancer drugs may further increase ROS to promote apoptosis, but can also enhance the metastasis of cancer cells. The effects of ROS homeostasis on cancer cells remain to be fully elucidated. In the present study, the effect of a reduction in manganese superoxide dismutase (MnSOD) on the migration and invasion of A431 cells was investigated. Our previous micro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 43 publications
(50 reference statements)
0
13
0
Order By: Relevance
“…ROS was reported to be majorly responsible for the downregulation of CAT via activation of PI3K/Akt signaling to reduce the activity of forkhead box protein O1 (FoxO1) in mesangial cells [ 93 ]. The reduced MnSOD activity in A431-P and A431-III cells promoted the metastatic ability of cancer cells [ 94 ]. As shown in Figure 7 , the levels of GPx in SH-SY5Y cells exposed to PtNPs, RA, and cisplatin for 24 h were 5, 6, and 4 μM, respectively, whereas PtNP and RA treatment resulted in significant reduction in GPx level (3 μM).…”
Section: Resultsmentioning
confidence: 99%
“…ROS was reported to be majorly responsible for the downregulation of CAT via activation of PI3K/Akt signaling to reduce the activity of forkhead box protein O1 (FoxO1) in mesangial cells [ 93 ]. The reduced MnSOD activity in A431-P and A431-III cells promoted the metastatic ability of cancer cells [ 94 ]. As shown in Figure 7 , the levels of GPx in SH-SY5Y cells exposed to PtNPs, RA, and cisplatin for 24 h were 5, 6, and 4 μM, respectively, whereas PtNP and RA treatment resulted in significant reduction in GPx level (3 μM).…”
Section: Resultsmentioning
confidence: 99%
“…In our earlier reports, we clearly demonstrated that A431-III cells, compared to A431-P cells, show higher migratory capacity and greater invasive potential [2,26,27,28,29,30,41]. To further characterize the migratory ability of A431-III cells as regulated by Src/Stat3/S100A7 signaling, we employed a wound-healing experiment.…”
Section: Resultsmentioning
confidence: 99%
“…In our earlier reports, we have established a highly invasive A431-III cell line from parental A431 cell line to investigate the migrative and invasive mechanism in cancer cells [26]. Lu and Qu are shown to efficiently increase catalase expression and reduction of H 2 O 2 production to decrease ROS stress in cancer cells [2]. Inhibition metastasis of A431-III cells by Lu and Qu were also observed.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, manganese superoxide dismutase (MnSOD), which is involved in ROS homeostasis, exhibits tumor-suppressive and cancer-promoting properties [75]. A reduced level of MnSOD in A431-P and A431-III cells has been shown to promote the metastatic ability of cancer cells [76]. In summary, the mechanism that increases ROS and decreases antioxidants lead to apoptosis in cancer cells.…”
Section: Effect Of Pdnps + Mlt On Antioxidant Marker Levelsmentioning
confidence: 99%